Interpretasi Data Geophysical Logging untuk Penentuan Sebaran Seam Batubara dalam Bentuk Model 3D - Batrisyia, Nisa; Djayus, Djayus; Supriyanto, Supriyanto (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2023)
In coal exploration activities, geophysical methods are usually used. One of the most accurate and effective geophysical methods that is still used in coal exploration today is the well logging method. The purpose of this research is to determine the distribution of coal seams in 3D based on well logging data. The data used in this study is secondary data which includes Gamma Ray Log data, Density Log data, and coordinate point data. Gamma Ray Log and Density Log data are interpreted to determine the types of lithology that make up the drill holes, especially coal. Based on the interpretation of the 3D model of the distribution of coal seams in each data it is known that in Seam A it tends to thin to the Southeast and thicken to the North-East, in Seam B it tends to thin out to the Southeast and Northeast, and in Seam C it tends to split to the North-West. and Northeast with a strike ranging from N 53ºE to N 116ºE with a dip ranging from 5º to 12º.